Hi there! Have questions about your homework? At Brainly, there are 60 million students who want to help each other learn. Questions are usually answered in less than 10 minutes. Try it for yourself by posting a question! :D

Hi there! Have questions about your homework? At Brainly, there are 60 million students who want to help each other learn. Questions are usually answered in less than 10 minutes. Try it for yourself by posting a question! :D

Let one no=x other no=x+6 accrdng to the statement.. x(x+6)=72 i.e x2(x square)+6x-72=0 using the method splitting the middle term... x2+6x-72=0 x2+12x-6x-72=0 takng common terms.. x(x+12-6()x+12)=0 i.e (x+12)(x-6)=0 i.e (x+12)=0 or (x-6)=0 therefor,.. x= -12 or 6 as value cannot be negative,we take the +ve value i.e 6 so x=6 substitute these values in the place of x one no=x=6 and other no=x+6 =6+6=12 and sum of these 2 nos=6+12 =18

u can even verify the answer as gvn theirproduct is 72 i.e 6*12=72